Common neural circuitry supporting volitional saccades and its disruption in schizophrenia patients and relatives - Camchong, Jazmin (2008)
BACKGROUND: People with schizophrenia and their biological relatives have deficits in executive control processes such as inhibition and working memory as evidenced by performance abnormalities on antisaccade (AS) and ocular motor delayed response (ODR) tasks. METHODS: The present functional magnetic resonance imaging (fMRI) study was conducted to investigate brain activity associated with these putative indices of schizophrenia risk by (i) directly comparing neural functioning in 15 schizophrenia patients, 13 of their first-degree biological relatives (primarily siblings), and 14 healthy participants, and (ii) assessing executive function associated with volitional saccades by using a combination of AS and ODR tasks. RESULTS: Behavioral data showed that patients and relatives both made more volitional saccade errors. Imaging data demonstrated that within the context of preserved activity in some neural regions in patients and relatives, there were two distinct patterns of disruptions in other regions. First, there were deficits observed only in the schizophrenia group (decreased activity in lateral FEF and SEF), suggesting a change associated with disease manifestation. Second, there were deficits observed in both patients and relatives (decreased activity in middle occipital gyrus, insula, cuneus, anterior cingulate, and BA10 in prefrontal cortex), indicating a potential association with disease risk. CONCLUSIONS: Results indicate that decreased brain activation in regions involved in managing and evaluating early sensory and attention processing may be associated with poor volitional saccade control and risk for developing schizophrenia.